Petroleum-based adhesive for prebaked anode and preparation method of petroleum-based adhesive
The preparation of petroleum-based adhesives through two-stage thermal polymerization method solves the problems of unstable quality and high cost of existing modified coal asphalt, and achieves the effect of improving the performance of pre-baked anode and reducing production costs.
Patent Information
- Application Number
- CN202411803959.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The modified coal asphalt used in the existing pre-baked anode production is unstable in quality, high cost, and difficult to improve the overall performance of the binder, affecting the use performance of the anode.
Petroleum-based adhesive was prepared by two-stage thermal polymerization method of residual oil and catalytic oil slurry. The residual oil was modified by medium and low temperature thermal polymerization, and further reacted with the catalytic oil slurry at high temperature to form a high residual carbon and low viscosity adhesive.
It improves the comprehensive performance of the binder, reduces production costs, extends the service life of the prebaked anode, and has a simple process and strong controllability. The properties of the obtained binder are basically the same as those of modified coal asphalt.
Smart Images

Figure BDA0005178718550000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of prebaked anode production, and in particular to a method for preparing a prebaked anode binder by polymerizing residual oil and catalytic oil slurry, and a petroleum-based binder prepared therefrom. Background Art
[0002] The production process of prebaked anode is to use petroleum coke, a byproduct of oil refineries, as aggregate, which accounts for more than 80% of the total mass of prebaked anode, and then use modified asphalt as a binder to manufacture prebaked anode. The cost of petroleum coke and binder accounts for about 75% of the production cost of prebaked anode. Its production uses petroleum coke, modified asphalt, etc. as raw materials, and forms carbon blocks after bonding with modified asphalt, and then calcined to obtain prebaked anode. The modified asphalt used in the existing prebaked anode production is basically modified coal tar pitch, and its quality directly affects the performance of the prebaked anode (such as bulk density, compressive strength, electrical conductivity and thermal conductivity, etc.), and these properties are closely related to the bonding performance, coking value and other properties of modified coal tar pitch.
[0003] At present, domestic electrolytic aluminum anode manufacturers generally use medium-temperature coal tar as a binder, but the impurity content in coal tar is high, the properties are unstable due to the influence of the place of origin, and the early pretreatment is difficult. In addition, with the capacity restrictions on the high-energy-consuming and high-emission steel industry in my country, the output of coal tar has decreased and the price has risen. The current price of coal tar used in the prebaked anode industry is 4,000-6,000 yuan / ton. Compared with coal tar, petroleum-based raw materials have the characteristics of low impurity content, wide source of raw materials, stable properties, and simple pretreatment process. Foreign countries have carried out research on the application of petroleum asphalt or a certain proportion of high-softening point petroleum asphalt mixed in medium-temperature coal tar as a binder. Therefore, the development and preparation of petroleum coke binders for prebaked anodes using petroleum-based raw materials can reduce the production cost of prebaked anodes and extend the service life of prebaked anodes.
[0004] Generally, in the production process of carbon anode, β resin, quinoline insoluble QI content and softening point are mainly used as indicators to characterize the superiority of asphalt. β resin is the most important binder component of coal tar pitch. The coke generated by β resin has a larger coking value, better coking performance, firm pore wall, fibrous structure, high strength and low resistance of the product. Therefore, the evaluation of binder asphalt pays special attention to the β component. Generally, the β component of coal tar pitch for aluminum carbon anode is more than 18%, and the corresponding coking value is required to be greater than 55%. Increasing QI can enhance the asphalt coke structure, but too high QI reduces the fluidity of asphalt; too low QI content will cause segregation and stratification of paste. At present, the QI content of coal tar pitch for aluminum carbon anode is generally required to be between 9% and 12%. Due to the complexity and variability of the composition and characteristics of coal tar pitch, it is difficult to strictly distinguish the decisive influence of a single asphalt component or characteristic on the quality of carbon anode. Therefore, it is necessary to comprehensively consider the influence of the comprehensive performance of asphalt on prebaked anode. How to improve the comprehensive performance of binder asphalt has become an urgent problem for prebaked anode manufacturers. Summary of the invention
[0005] One of the objects of the present invention is to provide a method for preparing a petroleum-based binder for prebaked anodes.
[0006] A second object of the present invention is to provide a petroleum-based adhesive prepared by the above method.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a method for preparing a petroleum-based binder for a prebaked anode, comprising the following steps:
[0009] The residual oil is mixed with an activator, and then the temperature is raised to carry out a first polymerization reaction, air is introduced into the reaction material during the heating process, and the reaction is followed by cooling to obtain a modified binder;
[0010] The catalytic oil slurry is desolidified and then subjected to vacuum distillation to cut out fractions above 350-400°C;
[0011] The obtained modified binder is mixed with the fraction after the reduced pressure distillation of the catalytic oil slurry, and then heated to melt, and then sealed and heated to carry out a second polymerization reaction, and then cooled after the reaction to obtain a petroleum-based binder for prebaked anodes.
[0012] The following is a detailed description:
[0013] Preparation of modified binder:
[0014] Residue oil refers to the residual oil extracted from the bottom of the vacuum tower after vacuum distillation using crude oil as raw material.
[0015] In some embodiments, the residual oil has the following properties: density (20°C) is 0.9916-1.0215 g / cm 3 , residual carbon content is 15.01-16.21wt%, and the softening point is 44.8-52.8℃.
[0016] In some embodiments, the activator is one or more selected from p-methylstyrene, p-methylbenzaldehyde or durene, and the amount used is 1-2.5 wt % of the amount of residual oil added.
[0017] In some embodiments, the residual oil is preheated before mixing with the activator, the preheating temperature is 60-80° C., and the preheating time is 30-40 min.
[0018] In some embodiments, heating for the first polymerization reaction includes: first heating freely to 100° C., then heating to 150-200° C. at a rate of 5-10° C. / min, and reacting at this temperature for 3-5 hours.
[0019] In some embodiments, the first polymerization reaction is carried out in a stirred reactor at normal pressure and low temperature.
[0020] In this step, the residual oil is cross-linked by adding an activator. Since the boiling point of the activator is relatively low, in order to prevent the activator from volatilizing at high temperature and causing the activator activity to decrease, a slow reaction at medium and low temperature is used to allow the chemical activator to promote molecular cross-linking of the branched alkane components in the residual oil. This prevents the activation from volatilizing and deactivating, and prevents excessive polymerization of small molecules.
[0021] In some embodiments, air is introduced into the reaction material in the stirred reactor at a flow rate of 3-5 L / min for 3-5 h. By introducing oxygen molecules, an oxidation reaction occurs to further promote cross-linking of components in the residual oil.
[0022] Preparation of fractions after vacuum distillation of catalytic oil slurry:
[0023] Catalytic slurry oil refers to the residual oil produced by the catalytic cracking unit of a refinery.
[0024] In some embodiments, the desolidification agent used in the desolidification treatment is a combination of demulsifiers, flocculants and other substances, and a commercially available product can be used, and its density (20°C) is ≥0.82g / cm 3 , viscosity (40℃) is 100-150mm 2 / s, freezing point ≤-25℃.
[0025] In some embodiments, the amount of the desolidifying agent used in the desolidification treatment is 300-500 mg / kg; and the standing time of the desolidification treatment is 36-48 hours.
[0026] The ash content of the oil slurry after desolidification is less than 0.1%, preferably the ash content of the oil slurry after desolidification is less than 0.03%.
[0027] In some embodiments, the process parameters of the reduced pressure distillation include: a reduced pressure temperature of 350° C.-550° C., and a pressure value of 0.1-0.5 MPa.
[0028] The cut fraction is preferably a fraction with a temperature of ≥400°C.
[0029] The catalytic oil slurry is rich in polycyclic aromatic hydrocarbons, which are beneficial to improve the softening point and viscosity of the reaction products in the subsequent reaction and reduce the production of quinoline insolubles. However, these polycyclic aromatic hydrocarbons are concentrated in the fraction ≥350°C. Therefore, the catalytic oil slurry needs to be vacuum distilled to extract the light components. At the same time, the adhesive has certain requirements on the ash content. If the ash content is too much, defects are likely to occur when bonding with the prebaked anode. Therefore, the catalytic oil slurry needs to be desolidified to reduce its ash content to an appropriate range.
[0030] Second polymerization reaction:
[0031] In some embodiments, the mixed mass ratio of the modified binder to the fraction after the vacuum distillation of the catalytic oil slurry is 3:1-2:1.
[0032] In some embodiments, the melting is heated slowly at a rate of 5-10°C / min.
[0033] In some embodiments, the temperature is raised to 300-350° C. after sealing, the time of the second polymerization reaction is 4-6 hours, and the pressure of the second polymerization reaction is 0.2-0.4 MPa.
[0034] In some embodiments, the second polymerization reaction is carried out in a micro-pressure high temperature stirred reactor.
[0035] After the reaction is completed, the reaction product is cooled naturally to obtain a prebaked anode binder with high carbon residue and low viscosity.
[0036] In a second aspect, the present invention provides a petroleum-based binder for prebaked anodes, which is prepared by the above-mentioned preparation method.
[0037] The obtained binder has a asphalt softening point of 105-110° C., quinoline insoluble matter of 7-11%, and ash content of less than 0.05%, thereby obtaining a binder that meets the requirements for use in prebaked anodes.
[0038] Technical effect:
[0039] (1) In order to ensure the comprehensive performance of the modified binder, firstly, a two-stage thermal polymerization method is adopted. The first stage is a medium-low temperature thermal polymerization method, which can prevent the volatilization of chemical active agents caused by high temperature and effectively ensure the activity of chemical active agents. First, chemical active substances are added to the residual oil to modify the small molecules in the residual oil by medium-low temperature thermal polymerization, which can improve the controllability of the thermal polymerization reaction and make the asphalt molecules polymerize in an orderly manner. Then, air is introduced during the reaction process, and the oxygen molecules in the air are used to provide an oxygen source for the reaction, so that the side chain alkanes in the residual oil can be broken and further thermally condensed. By controlling the time and flow rate of air introduction, it can be finally ensured that the residual oil does not undergo excessive cross-linking reaction and a suitable modified asphalt is obtained; at the same time, the residual oil molecules have more active sites and a greater degree of condensation, which is conducive to improving the residual carbon rate of asphalt; and the introduction of methyl substituent structure is beneficial to improving the fluidity of asphalt. The second stage of thermal polymerization mainly allows some unreacted groups of the first stage modified binder to continue to undergo thermal polymerization reaction with the treated catalytic oil slurry at high temperature to ensure that a pre-baked anode binder coal tar with high residual carbon and low viscosity is obtained.
[0040] (2) The catalytic oil slurry is desolidified and subjected to vacuum distillation to obtain a reaction component enriched in polycyclic aromatic hydrocarbons. In the second stage of polymerization, the polycyclic aromatic hydrocarbons participate in the reaction, which can increase the softening point and viscosity of the product without significantly increasing the QI insoluble matter of the product.
[0041] (3) The process of the present invention is simple, highly controllable, easy to operate, requires less reaction equipment, and the comprehensive performance of the resulting binder is stable. At the same time, residual oil and catalytic oil slurry are used as raw materials. Compared with modified coal tar, it has the advantages of low cost and basically the same product properties.
[0042] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0044] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0045] Catalytic slurry oil comes from the residual oil produced by the catalytic cracking unit of the refinery.
[0046] Test method: Softening point, quinoline insoluble matter and ash content are determined according to GB / T8730-98 method.
[0047] Example 1
[0048] (1) Weigh a certain amount of residual oil. The basic properties of the residual oil are as follows: density (20°C) is 0.9916 cm 3 , residual carbon content is 15.01wt%, and softening point is 52.8℃; then the residual oil is preheated at 60℃. After preheating for 30min, it is transferred into a polymerization kettle, and p-methylstyrene is added for stirring and mixing. After mixing evenly, the temperature is increased to 100℃, and then the temperature is increased to 150℃ at a rate of 5℃ / min after 100℃, and the reaction is carried out at this temperature for 3h. Air is introduced during the reaction, and the air flow rate is 3L / min. The air introduction time is 3h. After the reaction is completed, it is immediately cooled to room temperature to obtain a cross-linked modified adhesive.
[0049] (2) The catalytic oil slurry is subjected to desolidification treatment by adding a desolidification agent at a dosage of 300 mg / kg. The oil slurry is allowed to stand for 36 hours. After desolidification, the ash content of the oil slurry is less than 0.03%. The desolidified oil slurry is further subjected to vacuum distillation treatment to cut out a fraction above 350°C.
[0050] (3) The modified adhesive obtained in step (1) and the distillate oil obtained in step (2) are stirred and mixed in a ratio of 2:1. After being evenly mixed, they are slowly heated to melt at a rate of 5 minutes. After being sealed, the temperature is slowly raised to 300° C., and then a constant temperature reaction is carried out for 4 hours. During the reaction, the system pressure is maintained within the range of 0.2 MPa. After the reaction is completed, the reaction product is naturally cooled to obtain a prebaked anode adhesive with high carbon residue and low viscosity.
[0051] Example 2
[0052] (1) Weigh a certain amount of residual oil. The basic properties of residual oil are as follows: density (20℃) is 1.0215cm 3 , residual carbon content is 16.21wt%, and softening point is 52.8℃; then the residual oil is preheated at 80℃. After preheating for 30min, it is transferred into a polymerization kettle, and p-methylbenzaldehyde is added for stirring and mixing. After mixing evenly, the temperature is increased to 100℃, and then the temperature is increased to 200℃ at a rate of 10℃ / min after 100℃, and the reaction is carried out at this temperature for 5h. Air is introduced during the reaction, and the air flow rate is 5L / min. The air introduction time is 5h. After the reaction is completed, it is immediately cooled to room temperature to obtain a cross-linked modified binder.
[0053] (2) The catalytic oil slurry is subjected to desolidification treatment by adding a desolidification agent at a dosage of 500 mg / kg. The oil slurry is allowed to stand for 48 hours. After desolidification, the ash content of the oil slurry is less than 0.03%. The desolidified oil slurry is further subjected to vacuum distillation treatment to cut out a fraction ≥400°C.
[0054] (3) The modified adhesive obtained in step (1) and the distillate oil obtained in step (2) are stirred and mixed in a ratio of 3:1. After being evenly mixed, they are slowly heated to melt at a rate of 10 minutes. After being sealed, the temperature is slowly raised to 350° C., and then a constant temperature reaction is carried out for 6 hours. During the reaction, the system pressure is maintained within the range of 0.4 MPa. After the reaction is completed, the reaction product is naturally cooled to obtain a prebaked anode adhesive with high carbon residue and low viscosity.
[0055] Example 3
[0056] (1) Weigh a certain amount of residual oil. The basic properties of the residual oil are as follows: density (20°C) is 0.9975 cm 3 , residual carbon content is 15.921wt%, and softening point is 50.8℃; then the residual oil is preheated at 80℃. After preheating for 30min, it is transferred into a polymerization kettle, and p-methylstyrene is added for stirring and mixing. After mixing evenly, the temperature is increased to 100℃, and then the temperature is increased to 150℃ at a rate of 5℃ / min after 100℃, and the reaction is carried out at this temperature for 4h. Air is introduced during the reaction, and the air flow rate is 3L / min. The air introduction time is 4h. After the reaction is completed, it is immediately cooled to room temperature to obtain a cross-linked modified adhesive.
[0057] (2) The catalytic oil slurry is subjected to desolidification treatment by adding a desolidification agent at a dosage of 400 mg / kg. The oil slurry is allowed to stand for 48 hours. After desolidification, the ash content of the oil slurry is less than 0.03%. The desolidified oil slurry is further subjected to vacuum distillation treatment to cut out a fraction ≥400°C.
[0058] (3) The modified adhesive obtained in step (1) and the distillate oil obtained in step (2) are stirred and mixed in a ratio of 3:1. After the mixture is evenly mixed, the mixture is slowly heated to melt at a rate of 5 minutes. After sealing, the temperature is slowly raised to 300° C., and then a constant temperature reaction is performed for 6 hours. During the reaction, the system pressure is maintained within the range of 0.3 MPa. After the reaction is completed, the reaction product is naturally cooled to obtain a prebaked anode adhesive with high carbon residue and low viscosity.
[0059] Example 4
[0060] (1) Weigh a certain amount of residual oil. The basic properties of the residual oil are as follows: density (20°C) is 0.9916 cm 3, residual carbon content is 15.01wt%, and softening point is 44.8℃; then the residual oil is preheated at 80℃. After preheating for 30min, it is transferred into a polymerization kettle, and tetramethylbenzene is added for stirring and mixing. After mixing evenly, the temperature is increased to 100℃, and then the temperature is increased to 150℃ at a rate of 5℃ / min after 100℃, and the reaction is carried out at this temperature for 5h. Air is introduced during the reaction, and the air flow rate is 4L / min. The air introduction time is 5h. After the reaction is completed, it is immediately cooled to room temperature to obtain a cross-linked modified adhesive.
[0061] (2) The catalytic oil slurry is subjected to desolidification treatment by adding a desolidification agent at a dosage of 500 mg / kg. The oil slurry is allowed to stand for 36 hours. After desolidification, the ash content of the oil slurry is less than 0.03%. The desolidified oil slurry is further subjected to vacuum distillation treatment to cut out a fraction ≥350°C.
[0062] (3) The modified adhesive obtained in step (1) and the distillate oil obtained in step (2) are stirred and mixed in a ratio of 2:1. After being evenly mixed, they are slowly heated to melt at a rate of 100 min. After being sealed, the temperature is slowly raised to 350° C., and then a constant temperature reaction is carried out for 5 hours. During the reaction, the system pressure is maintained within the range of 0.2 MPa. After the reaction is completed, the reaction product is naturally cooled to obtain a prebaked anode adhesive with high carbon residue and low viscosity.
[0063] Comparative Example 1
[0064] Weigh a certain amount of residual oil. The basic properties of residual oil are as follows: density (20℃) is 0.9916cm 3 , residual carbon content is 15.01wt%, and softening point is 44.8℃; then preheat the residual oil at 80℃. After preheating for 30min, transfer it into a polymerization kettle, add tetramethylbenzene and stir to mix. After mixing evenly, start heating to 100℃, and then heat to 320℃ at a rate of 5℃ / min after 100℃, and react at this temperature for 4h. After the reaction is completed, cool it to room temperature immediately to obtain a cross-linked modified binder.
[0065] Comparative Example 2
[0066] Weigh a certain amount of residual oil. The basic properties of residual oil are as follows: density (20℃) is 0.9916cm 3, the residual carbon content is 15.01wt%, and the softening point is 44.8℃; the residual oil is preheated at 80℃. After preheating for 30min, it is transferred into a polymerization kettle, and tetramethylbenzene is added for stirring and mixing. After mixing evenly, the temperature begins to rise to 100℃, and after 100℃, the temperature rises to 150℃ at a rate of 5℃ / min, and the reaction is carried out at this temperature for 5h. After the reaction, the cut catalytic oil slurry is mixed in a ratio of 2:1, and after mixing evenly, it is slowly heated to melt at a rate of 100min. After sealing, the temperature is slowly raised to 350℃, and then a constant temperature reaction is carried out for 5h. During the reaction, the system pressure is maintained within the range of 0.2MPa. After the reaction is completed, the reaction product is naturally cooled.
[0067] Table 1 Performance analysis results of examples and comparative examples
[0068]
[0069] As can be seen from Table 1, the emulsification point, quinoline insoluble matter and ash content of the binder for prebaked anodes obtained by the present invention are similar to the modified coal tar pitch index dedicated to prebaked anodes, indicating that the product obtained by the process using residual oil and catalytic oil slurry as raw materials meets the demand for binders for prebaked anodes. At the same time, the performance of the binder obtained by using residual oil as raw material only by a one-step method is poor, and the softening point and quinoline insoluble matter do not meet the index requirements. The product obtained by the two-step method of residual oil and catalytic oil slurry without oxidative polycondensation has a softening point and quinoline insoluble matter index that are not as good as the product in the embodiment.
[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a petroleum-based binder for prebaked anodes, characterized in that: The following steps are involved: The residual oil is mixed with an activator, and then the temperature is raised to carry out a first polymerization reaction, air is introduced into the reaction material during the heating process, and the reaction is followed by cooling to obtain a modified binder; The catalytic oil slurry is desolidified and then subjected to vacuum distillation to cut out fractions above 350-400°C; The obtained modified binder is mixed with the fraction after the reduced pressure distillation of the catalytic oil slurry, and then heated to melt, and then sealed and heated to carry out a second polymerization reaction, and then cooled after the reaction to obtain a petroleum-based binder for prebaked anodes.
2. The method according to claim 1, characterized in that The residual oil has the following properties: density (20℃) is 0.9916-1.0215g / cm 3 , residual carbon content is 15.01-16.21wt%, and the softening point is 44.8-52.8℃.
3. The method according to claim 1, characterized in that The activator is one or more selected from p-methylstyrene, p-methylbenzaldehyde or durene, and the amount used is 1-2.5wt% of the amount of the residual oil added.
4. The method according to claim 1, characterized in that The first polymerization reaction is carried out by heating the temperature to 100° C. first, then heating the temperature to 150-200° C. at a heating rate of 5-10° C. / min, and reacting at this temperature for 3-5 hours.
5. The method according to claim 1, characterized in that The air flow rate is 3-5L / min, and the air supply time is 3-5h.
6. The method according to claim 1, characterized in that The amount of the desolidifying agent added for the desolidification treatment is 300-500 mg / kg; the standing time for the desolidification treatment is 36-48 hours.
7. The method according to claim 1, characterized in that The mixing mass ratio of the modified binder to the fraction after the reduced pressure distillation of the catalytic oil slurry is 3:1-2:
1.
8. The method according to claim 1, characterized in that Slowly heat and melt at a rate of 5-10°C / min; after sealing, heat to 300-350°C, the second polymerization reaction time is 4-6h, and the second polymerization reaction pressure is 0.2-0.4MPa.
9. A petroleum-based binder for prebaked anodes, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. The petroleum-based binder for prebaked anodes according to claim 9, characterized in that: The asphalt softening point of the petroleum-based binder for the prebaked anode is 105-110° C., the quinoline insoluble matter is 7-11%, and the ash content is less than 0.05%.
Citation Information
Patent Citations
Resin-based prebaked anode and preparation process thereof
CN114318421A
Application of deoiled asphalt in preparation of prebaked anode adhesive and prebaked anode
CN117756089A
Method for producing petroleum-coal tar pitch binder
WO2020256590A1
Cited By
Process system and method for continuously producing electrode binder by taking unconverted oil slurry in slurry reactor as raw material
CN121022440A